Introgression of a Danbaekkong high-protein allele across different genetic backgrounds in soybean - Souza, Renan; Rouf Mian, M. A.; Vaughn, Justin N.; Li, Zenglu (Frontiers in Plant Science, 2023)
Soybean meal is a major component of livestock feed due to its high content and quality of protein. Understanding the genetic control of protein is essential to develop new cultivars with improved meal protein. Previously, a genomic region on chromosome 20 significantly associated with elevated protein content was identified in the cultivar Danbaekkong. The present research aimed to introgress the Danbaekkong high protein allele into elite lines with different genetic backgrounds by developing and deploying robust DNA markers. A multiparent population consisting of 10 F5-derived populations with a total of 1115 recombinant inbred lines (RILs) was developed using 'Benning HP' as the donor parent of the Danbaekkong high protein allele. A new functional marker targeting the 321 bp insertion in the gene Glyma.20g085100 was developed and used to track the Danbaekkong high protein allele across the different populations and enable assessment of its effect and stability. Across all populations, the high protein allele consistently increased the content, with an increase of 3.3% in seed protein. One hundred and three RILs were selected from the multiparent population for yield testing in five environments to assess the impact of the high protein allele on yield and to enable the selection of new breeding lines with high protein and high yield. The results indicated that the high protein allele impacts yield negatively in general, however, it is possible to select high yielding lines with high protein content. An analysis of inheritance of the Chr 20 high protein allele in Danbaekkong indicated that it originated from a G. soja line (PI 163453) and is the same as other G. soja lines studied. A survey of the distribution of the allele across 79 G. soja accessions and 35 G. max ancestors of North American soybean cultivars showed that the high protein allele is present in all G. soja lines evaluated but not in any of the 35 North America soybean ancestors. These results demonstrate that G. soja accessions are a valuable source of favorable alleles for improvement of protein composition.